A Rare Complication of TEVAR Performed for Complex Acute Stanford B Aortic Dissection - Awad, George; Zardo, Patrick; Baraki, Hassina; Kutschka, Ingo (The Thoracic and Cardiovascular Surgeon Reports, 2017)
Management of aortic dissection with a novel endovascular technique known as thoracic endovascular aortic repair (TEVAR) paired with surgical debranching as a less invasive alternative to conventional repair has gained widespread acceptance. However, experience for complicated, Stanford type B dissection involving the aortic arch is still limited.
Keywords: acute Stanford B aortic dissection; TEVAR; debranching